Clinical study of neurological presentation of diabetes mellitus in a tertiary care hospital - Sharma, Sadhna; Pasha, Shaik Afsar; Mohidden, Mohammad Khawja; Srikanth, E. (International Journal of Research in Medical Sciences, 2020)
Background: A wide range of commotions affecting the central and peripheral nervous systems, either directly or indirectly, may be observed in patients with diabetes mellitus. The spectrum of neurological complications among diabetes are quite varied. Methods: Authors conducted a Cross-sectional prospective observational study to study different neurological manifestations of diabetes mellitus. at NRI General Hospital, Chinakakani, Guntur District, Andhra Pradesh. The selected patients were studied in detail with history and physical examination. The investigations included Fasting Blood Sugar (FBS), Postprandial Blood Sugar (PPBS), Glycosylated Hemoglobin (HbA1C). Results: A total of 100 subjects were included in the final analysis. Majority of participants were aged between 46 to 65 years, and 55% of them were males. Only 13% of the participants had HBA1c value below 7.5 gm%. Out of 100 participants, 82% participants had diabetic peripheral neuropathy. A total of 6 subjects had cranial neuropathy, with 5% participants having 3rd nerve and one participant had 6th nerve. Involuntary movements (Chorea) was present in 4% of patients. Among the people with Seizures, 6% participants had Hyperglycemic, and 2% participants had Hypoglycemic seizures. Out of 100 participants, 7 participants had dysautonomia. Conclusions: Peripheral neuropathy was the most common neurological manifestation among the diabetic population. The other key neurological abnormalities include cranial nerve palsy, dysautonomia, seizures and Chorea. Clinicians need to be aware the entire spectrum of neurological abnormalities among patients with type 2 Diabetes.